2020
DOI: 10.1038/s41396-020-00853-2
|View full text |Cite
|
Sign up to set email alerts
|

Loss of a pyoverdine secondary receptor in Pseudomonas aeruginosa results in a fitter strain suitable for population invasion

Abstract: The rapid emergence of antibiotic resistant bacterial pathogens constitutes a critical problem in healthcare and requires the development of novel treatments. Potential strategies include the exploitation of microbial social interactions based on public goods, which are produced at a fitness cost by cooperative microorganisms, but can be exploited by cheaters that do not produce these goods. Cheater invasion has been proposed as a 'Trojan horse' approach to infiltrate pathogen populations with strains deployin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…Our interpretations are supported by molecular studies on the laboratory strains P. aeruginosa PAO1 (González et al, 2021) and P. protegens Pf-5 (Sexton et al, 2017), which revealed that cognate receptors are preferred over noncognate receptors and that noncognate receptors are conditionally expressed upon sensing of a heterologous pyoverdine. How this sensing exactly works is unclear, but it comes with a time delay (Sexton et al, 2017), probably further reducing the iron-uptake efficiency of noncognate relative to cognate receptors.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our interpretations are supported by molecular studies on the laboratory strains P. aeruginosa PAO1 (González et al, 2021) and P. protegens Pf-5 (Sexton et al, 2017), which revealed that cognate receptors are preferred over noncognate receptors and that noncognate receptors are conditionally expressed upon sensing of a heterologous pyoverdine. How this sensing exactly works is unclear, but it comes with a time delay (Sexton et al, 2017), probably further reducing the iron-uptake efficiency of noncognate relative to cognate receptors.…”
Section: Discussionsupporting
confidence: 59%
“…Our interpretations are supported by molecular studies on the laboratory strains P . aeruginosa PAO1 (González et al., 2021 ) and P . protegens Pf‐5 (Sexton et al., 2017 ), which revealed that cognate receptors are preferred over noncognate receptors and that noncognate receptors are conditionally expressed upon sensing of a heterologous pyoverdine.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this finding, we previously identified a TS-resistant but thiocillin-sensitive clinical isolate, C0379, missing ~800 bp from the 5' region of fpvB, suggesting that it may have once produced functional FpvB (Ranieri et al, 2019). ∆fpvB mutants are also fitter than WT cells when treated with the antibiotic gentamicin (González et al, 2021). Its absence may reduce the metabolic burden on cells living in stressful environments whether due to nutrient limitation or antibiotic stress.…”
Section: Discussionmentioning
confidence: 68%
“…A different type of “Trojan horse” approach is represented by the “cheater invasion”, in which MDR pathogen populations were infiltrated by strains with built-in weaknesses ( Figure 2 ). For example, recently, antibiotic-resistant P. aeruginosa strains were replaced by the antibiotic-sensitive P. aeruginosa PAO1; this result was achieved by deleting its FpvB PVD receptor, which gives them a selective advantage [ 133 ].…”
Section: Biotechnological Potential Of Pvdsmentioning
confidence: 99%